Social Exclusion versus Culture - Determinants of Romani settlement Dwellers` Social behaviour. Research project - Kozubík, Michal (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This contribution deals with scientific goals for whole period of this project, its characte-ristic, realisation outputs and output user and description of applied methods and their explanation. Stereotypes and prejudices against differences, nations and national minorities are spread in lay society and they are supported by massmedial campaign and society accepts them as the fact and the true.
Keywords: Romani national minority; social exclusion; poverty; culture; project; Romani segregated communities; romska mniejszość narodowa; wykluczenie społeczne; ubóstwo; kultura; projekt; segregowana społeczność romska